Q: How do you show your work for 3sqrt x -5 equals 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Ahexagon = 3sqrt(3)s2/2 = 3sqrt(3)(82)/2 = 96sqrt(3)

3sqrt(80)= 26.8======

2n - 3 = 5Add 3 to each side:2n = 8Divide each side by 2:n = 4

(x-5)^(1/3) = 3; (x-5) = 3^3 = 27; x = 27+5=32

1.5

Related questions

3sqrt(3) - sqrt(45) + 3sqrt(13)= 3sqrt(3) - 3sqrt(5) + 3sqrt(13) = 3*[sqrt(3) - sqrt(5) + sqrt(13)] where the expression in parenthesis cannot be simplified.The value is 9.3046, approx.

Ahexagon = 3sqrt(3)s2/2 = 3sqrt(3)(82)/2 = 96sqrt(3)

sqrt(18) = sqrt(9*2)= sqrt(9)*sqrt(2) = +/-3sqrt(2) -3sqrt(2) - 7sqrt(18) = -3sqrt(2) -/+7*3sqrt(2) = -3sqrt(2) -/+21sqrt(2) = -24sqrt(2) or 18sqrt(2).

Well if you have to show you're work, you do 7X123 which equals 861, and then you do 861-3 and that equals 858

3sqrt(- 1 ) = 3i --------

3sqrt(80)= 26.8======

3sqrt(5) = 6.708 approx.

3sqrt(- 1 ) = 3i --------

102

3sqrt(8) = 3sqrt(2 x 2 x2) = 3sqr(2) X sqrt(2) x sqrt(2) = 3X 2 x sqrt(2) Remember sqrt(2) X sqrt(2) = 2 Hence 6sqrt(2) = 3sqrt(8)

2n - 3 = 5Add 3 to each side:2n = 8Divide each side by 2:n = 4

(x-5)^(1/3) = 3; (x-5) = 3^3 = 27; x = 27+5=32